2009
DOI: 10.1523/jneurosci.4390-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Beclin 1 Gene Transfer Activates Autophagy and Ameliorates the Neurodegenerative Pathology in α-Synuclein Models of Parkinson's and Lewy Body Diseases

Abstract: Accumulation of the synaptic protein ␣-synuclein (␣-syn) is a hallmark of Parkinson's disease (PD) and Lewy body disease (LBD),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
473
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 552 publications
(495 citation statements)
references
References 68 publications
19
473
1
2
Order By: Relevance
“…Atg5 was unchanged, in contrast to, for example, adenovirus-induced autophagy (61) but similar to brains of patients and mouse models of AD and α-synucleinopathy (62). Masliah and colleagues showed that lentiviral beclin-1 overexpression reduces amyloid pathology in APP transgenic mice, as well as α-synuclein accumulation and degenerate pathology in α-synuclein overexpression models in vitro and in vivo; these data suggest a role of beclin-1 in autophagy induction and possibly targeting excess misfolded protein to the autophagy pathway (63,64). Beclin-1 was reduced in TPrP-treated neurons and in scrapie-infected brains, suggesting a deleterious exhaustion of this early player of the autophagic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Atg5 was unchanged, in contrast to, for example, adenovirus-induced autophagy (61) but similar to brains of patients and mouse models of AD and α-synucleinopathy (62). Masliah and colleagues showed that lentiviral beclin-1 overexpression reduces amyloid pathology in APP transgenic mice, as well as α-synuclein accumulation and degenerate pathology in α-synuclein overexpression models in vitro and in vivo; these data suggest a role of beclin-1 in autophagy induction and possibly targeting excess misfolded protein to the autophagy pathway (63,64). Beclin-1 was reduced in TPrP-treated neurons and in scrapie-infected brains, suggesting a deleterious exhaustion of this early player of the autophagic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, activation of autophagy by rapamycin treatment increases clearance of a-synuclein aggregates in cells that express mutant a-synuclein 105 . The overexpression of beclin-1 ameliorates the accumulation of a-synuclein by enhancing lysosomal function and reducing the deficits in the autophagic pathway 155 . Pharmacological autophagy activation also ameliorates HD phenotype 88,123,124 .…”
Section: Loss Of Clearance Mechanisms As a Determinant Of Ageingmentioning
confidence: 99%
“…Therefore, autophagy can prevent the emergence of neurodegenerative diseases. Indeed, autophagy protects against aggregation-prone mutant proteins in spinocerebellar ataxia, mutated forms of α-synuclein in Parkinson's disease, mutant Huntingtin in Huntington's disease, tau mutants that cause frontotemporal dementia, pathogenic intraneuronal amyloid beta in Alzheimer disease brain and polyglucosan inclusion bodies in Lafora disease [162,196,[198][199][200][201][202]. Interestingly, most of these neurodegenerative diseases are associated with decreased Beclin-1 levels, which might account for the impaired autophagic clearance.…”
Section: Autophagy In Other Diseasesmentioning
confidence: 99%